2021
DOI: 10.1080/1359432x.2021.1968375
|View full text |Cite
|
Sign up to set email alerts
|

On the destructiveness of laissez-faire versus abusive supervision: a comparative, multilevel investigation of destructive forms of leadership

Abstract: Different forms of destructive leadership are prevalent in organizations, but rarely studied together. Additionally, most studies take an individual-level view on the consequences of destructive leadership. However, while most supervisors lead teams, it remains unclear how destructive leadership behaviours affect team processes and outcomes from a multilevel perspective. Building on this premise, we analysed the relationship of abusive supervision and laissez-faire leadership with OCB on the individual and tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 95 publications
(197 reference statements)
1
15
0
1
Order By: Relevance
“…Active and passive destructive behaviours are often studied in isolation and in separate studies. By contrasting the antecedents to active and passive destructive behaviours we answer the calls in the literature to compare and differentiate different forms of destructive leadership (Klasmeier et al, 2021; Schyns & Schilling, 2013), which is important to accumulate knowledge of their unique causes and effects (Klasmeier et al, 2021). It also aligns well with the resource perspective (Wang et al, 2010) and COR theory (Hobfoll, 1989; Hobfoll et al, 2018), which suggest that when resources are outstretched or exhausted, individuals enter a defensive mode that may be either aggressive or passive to preserve the self.…”
Section: Introductionmentioning
confidence: 99%
“…Active and passive destructive behaviours are often studied in isolation and in separate studies. By contrasting the antecedents to active and passive destructive behaviours we answer the calls in the literature to compare and differentiate different forms of destructive leadership (Klasmeier et al, 2021; Schyns & Schilling, 2013), which is important to accumulate knowledge of their unique causes and effects (Klasmeier et al, 2021). It also aligns well with the resource perspective (Wang et al, 2010) and COR theory (Hobfoll, 1989; Hobfoll et al, 2018), which suggest that when resources are outstretched or exhausted, individuals enter a defensive mode that may be either aggressive or passive to preserve the self.…”
Section: Introductionmentioning
confidence: 99%
“…Leaders being absent, inactive, and avoidant when their active involvement is needed (laissez-faire leadership) [37,38] is commonly treated as a passive form of destructive leadership [37,39]. Research has shown that both active and passive forms of destructive leadership are detrimental to both organisational effectiveness and employees' wellbeing [26,27,34,[39][40][41][42][43].…”
mentioning
confidence: 99%
“…Thus, when we refer to high abusive supervision in this paper, it is high in relative terms. In absolute terms, the level of reported abuse in both studies was low-medium at best, not unlike levels that are typically reported in the literature (Klasmeier et al, 2021;Mawritz et al, 2014;Mitchell & Ambrose, 2007;Tepper, 2000). We suspect that response-style biases such as impression management or social desirable responding patterns might contribute to an under-reporting of leader abuse.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 59%